The efficacy and safety of intra-articular botulinum toxin type A injection for knee osteoarthritis: A meta‐analysis of randomized controlled trials. (1st March 2023) - Wang, Chen; Zhao, Jinpeng; Gao, Fang; Jia, Min; Hu, Luoman; Gao, Chengfei
Abstract: The purpose of this study was to investigate the efficacy and safety of intra-articular Botulinum Toxin type A (BTA) injection in the management of patients with knee osteoarthritis (KOA). The literature retrieval was conducted based on PRISMA guidelines. Databases including Pubmed, Web of science, EMBASE, and Cochrane Library were searched to identify RCTs that comparing the effects of intra-articular BTA injection with control interventions on patients with KOA. The primary outcomes involved pain and function improvements as well as the occurrence of adverse events. Seven RCTs comprising 548 participants were included in this meta-analysis. Compared with the control group, BTA injection exhibited greater pain reduction at 4 weeks posttreatment (SMD = −0.86, 95% CI [−1.52, −0.19], p = 0.011), but not 8–24 weeks posttreatment (wk 8, SMD = −0.53, 95% CI [−1.21, 0.15], p = 0.127; wk 12, SMD = −0.34, 95% CI [−0.73, 0.04], p = 0.081; wk 24, SMD = −0.65, 95% CI [−1.52, 0.22], p = 0.144). Additionally, no differences were found between BTA injection versus control intervention on functional improvement at all time points assessed (wk 4, WMD = −5.16, 95% CI [−12.31, 2.00], p = 0.158; wk 8, WMD = −0.98, 95% CI [−5.66, 3.71], p = 0.683; wk 12, WMD = −2.52, 95% CI [−7.54, 2.50], p = 0.325); wk 24, WMD = −3.66, 95% CI [−14.09, 6.76], p = 0.491). There was no significant difference in adverse event rate between the BTA and control group (OR = 0.88, 95% CI [0.24, 3.18], p = 0.843). This meta-analysis suggests that intra-articular BTA injection could be an efficious and safe strategy for analgesic treatment of KOA. However, evidence is limited due to the small number and heterogeneity of included studies, this urges further and stronger trials to confirm our findings. Graphical abstract: Image 1 Highlights: This was the first meta-analysis to investigate the efficacy and safety of BTA injection in the management of KOA. The evidence showed BTA injection could be considered as an effective and safe choice for pain relief of patients with KOA. The number of studies and sample sizes included in systematic review was limited and no subgroup analysis was performed. Heterogeneity existed among the included studies, which may be a possible limitation.